The Internalization of Bugis-Makassar Cultural Ethical Values As a Strategy for Preventing Corruption In South Sulawesi - Hasni Hasni; Patahuddin Patahuddin; Bustan Bustan; Asmunandar Asmunandar; Ilma Indiariasri Pratiwi (UIN Fatmawati Sukarno Bengkulu, 2026)
Corruption, as an extraordinary crime, remains a serious problem in Indonesia, including in South Sulawesi, despite various legal measures having been implemented. This highlights the need for reinforcement through a cultural approach grounded in ethical values. This study aims to analyze ethical values within the Bugis-Makassar cultural philosophy and their relevance to corruption prevention. The method employed is qualitative, involving a literature review through documentation and thematic analysis. The findings indicate that the values of Sipakatau’, Sipakalebbi’, and Sipakainge’ play a strategic role in shaping individuals of integrity and ethical character. The value of Sipakatau’ fosters respect for others’ rights; Sipakalebbi’ strengthens a culture of appreciation and social responsibility; while Sipakainge’ functions as a social control mechanism through a culture of mutual reminders. The integration of these three values has the potential to cultivate moral awareness and a sense of shame (Siri’), which serve as a bulwark against corrupt behavior. The contribution of this research is to offer a framework for corruption prevention based on local wisdom as a complement to formal legal approaches.